Annual general meeting SOPHYS 2025 / Nur Shareena Maisarah Mohd Ghazali, Aqhli Waheeda Zainal and Gurmeet Kaur Surindar Singh - Mohd Ghazali, Nur Shareena Maisarah; Zainal, Aqhli Waheeda; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2025)
The Society of Pharmacy Students (SOPHYS) Universiti Teknologi MARA (UiTM) Puncak Alam batch 2023/2024 organised the annual general meeting SOPHYS 2025. This event took place at DK9, Faculty of Pharmacy, UiTM Puncak Alam, on 31 December 2024.